The ‘Scottish approach’ to global health: A scoping review of the framing of global health partnerships - Kristina Kim; Kaveri Qureshi; Emily Adrion; Goran Zangana; Sudeepa Abeysinghe (Global Public Health, 2025)
The narrative framings of partnerships and interventions in global health shed light on actors’ conceptualisations of international development. Ideas of equity and justice in North–South partnerships are increasingly centred in international development and global health policy approaches. However, the extent to which these are evident within practice requires further investigation. This paper critically examines published work from health actors based in Scotland conducted within low – and middle-income countries (LMICs), under a Scottish government policy context currently promoted as engaging in a novel approach to international development. The paper uses a scoping review to analyse Scottish actors’ engagement and framing of global health interventions and partnerships with LMIC actors. A majority of the texts discussed Scottish-affiliated global health partnerships and/or interventions in the Malawian medical education and clinical medicine context and focused on capacity building and knowledge transfer. Authors of included documents characterised the ‘Scottish approach’ to partnership as rejecting the traditional donor-aid model and championing ideas of collaboration, reciprocity and equity in partnership. Yet simultaneously, most works described partnerships that positioned Scottish actors as the sources of expertise with partner country actors as beneficiaries, replicating the donor-recipient aid model. Additionally, the framing of partnership activities frequently deployed historical narrative frames.